Comprehensive Evaluation of the Nutritional Properties of Different Germplasms of Polygonatum cyrtonema Hua - Mei Lu; Luping Zhang; Shixin Kang; Fengxiao Ren; Luyun Yang; Qingyou Zhang; Qiaojun Jia (Foods, 2024)
Polygonatum cyrtonema Hua, an edible resource and medical material, is mainly consumed as a food in China. However, few published studies have comprehensively assessed its nutritional components. In this study, the proximate, carbohydrate, and dietary fiber contents as well as the mineral, vitamin, and amino acid compositions of five sources of P. cyrtomena grown in Yuhang district, Hangzhou city, Zhejiang province, were investigated. The nutritional profile of the five germplasms was investigated using analytical chemistry methods. All germplasms had a low starch content and contained greater amounts of carbohydrates (23.25–34.29%), protein (2.96–5.40%), Ca (195.08–282.08 mg/100 g), Fe (29.68–59.37 mg/100 g), and vitamin C (60.49–149.86 mg/100 g) in comparison to ginger, yam, and potatoes. The polysaccharide content ranged from 16.92% to 28.48%, representing the main source of carbohydrates. Fructose, a desirable sweetener, was the most abundant monosaccharide, representing 1.06% to 4.88% of the content. P. cyrtonema was found to be high in dietary fiber, with pectin and resistant starch being the major soluble components and hemicellulose being the dominant insoluble dietary fiber. A correlation analysis (CA) revealed significant correlations for the carbohydrate components and dietary fiber fractions with other nutrients. A principal component analysis (PCA) identified significant differences between the nutritional characteristics of the five germplasms, with Huanggang having the highest comprehensive quality scores. Moreover, ten nutrient components were selected as potential indicators that could be used to further evaluate the nutritional quality of P. cyrtomena. Our results demonstrate the rich nutrient composition and characteristics of P. cyrtonema and provide a valuable reference for the future development and utilization of Polygonatum.